Lagrange Spaces with (γ, β)-Metric. (30th January 2013) - Shukla, Suresh K.; Pandey, P. N.
Abstract : We study Lagrange spaces with ( γ, β ) -metric, where γ is a cubic metric and β is a 1-form. We obtain fundamental metric tensor, its inverse, Euler-Lagrange equations, semispray coefficients, and canonical nonlinear connection for a Lagrange space endowed with a ( γ, β ) -metric. Several other properties of such space are also discussed.